1987
DOI: 10.1210/jcem-65-4-634
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acids Block Growth Hormone (GH) Releasing Hormone-Stimulated GH Secretion in Man Directly at the Pituitary*

Abstract: Increases in plasma FFA levels inhibit GH responses to a variety of pharmacological and physiological stimuli. To gain further insight into the mechanism by which FFA exert their effect, we studied the plasma GH responses to GHRH-(1-44) (1 microgram/kg, iv) in normal subjects in whom plasma FFA levels were raised by a lipid-heparin infusion (250 mL 10% Intralipid plus 2500 U heparin). Paired tests were performed in 10 normal subjects, with and without lipid-heparin pretreatment. Lipid-heparin infusion from -30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
1
6

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(117 citation statements)
references
References 29 publications
10
100
1
6
Order By: Relevance
“…12,13,17,18,21,23,40 Con®rm-ing the metabolic pathogenesis of GH de®ciency in obesity there is the well known evidence that spontaneous and stimulated GH secretion are restored by weight loss 2,6 and that a clear inverse relationship exists between GH secretion and body mass. 2 From a diagnostic point of view, it has to be considered that the diagnosis of GH de®ciency in adulthood is still a matter of debate though there is clear evidence for usefulness of rhGH replacement.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,17,18,21,23,40 Con®rm-ing the metabolic pathogenesis of GH de®ciency in obesity there is the well known evidence that spontaneous and stimulated GH secretion are restored by weight loss 2,6 and that a clear inverse relationship exists between GH secretion and body mass. 2 From a diagnostic point of view, it has to be considered that the diagnosis of GH de®ciency in adulthood is still a matter of debate though there is clear evidence for usefulness of rhGH replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Its administration to both animals and humans induces an increase in serum concentrations of glycerol and NEFA. These latter, in turn, exert a negative feedback control on GH secretion acting at the pituitary 101 and the hypothalamus, probably by enhancing SRIH release. 102 In fact, in normal subjects, the increase in NEFA serum concentrations blunts the somatotropin responses to both GHRH and suprapituitary stimuli.…”
Section: Nefamentioning
confidence: 99%
“…FFA elevations reduce or block GH secretion stimulated by a variety of stimuli or conditions, such as FFA depression, hypoglycemia, physical exercise or administration of GH releasing hormone (GHRH) or GHRP-6. 3,4 There is now compelling evidence indicating that the FFA blockade of GH secretion is exerted at the pituitary level, probably by direct inhibition of somatotroph function. 4,5 The effect of FFA on GH secretion is exerted at physiological levels, since reduction in circulating FFA levels following administration of acipimox, per se stimulates basal GH secretion as well as increasing GH responses to different GH secretagogues in normal subjects.…”
Section: Free Fatty Acids and Gh Secretionmentioning
confidence: 99%
“…3,4 There is now compelling evidence indicating that the FFA blockade of GH secretion is exerted at the pituitary level, probably by direct inhibition of somatotroph function. 4,5 The effect of FFA on GH secretion is exerted at physiological levels, since reduction in circulating FFA levels following administration of acipimox, per se stimulates basal GH secretion as well as increasing GH responses to different GH secretagogues in normal subjects. 6,7 Since obesity is associated with abnormal elevations in both fasting and postprandial FFA concentrations, it has been suggested that elevated FFA could be one of the mechanisms responsible for impaired GH secretion in obese subjects.…”
Section: Free Fatty Acids and Gh Secretionmentioning
confidence: 99%